Some Reconquests of Journalism - Arrese, Ángel (2022)
The future of newspapers and journalism is one of the key themes in the current debates around the media. The severe economic and identity crisis being experienced in the sector have raised all the alarms, and every newspaper is rethinking what to do to survive. This article raises the need for journalism to “reconquer” some land lost in these times of transformation. The reconquests that are proposed affect to different aspects of journalism, both from a professional and business point of view.